Pseudo-Otoritas dalam Ruang Kebijakan. Studi Kasus Intervensi Ormas terhadap Sektor Usaha di Kota Makassar - Muhammad Suyuti; Suardi Muklis; Andi Bahrun Syam; Hermansyah Hermansyah; Wahyudin Zuhri (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This research focuses on the involvement of community organizations (CSOs) in business activities in Makassar City, emphasizing the dynamics of power relations that develop outside the formal framework of the state. In daily practice, CSOs frequently conduct inspections, symbolic enforcement, and even intimidation against business actors despite lacking official government mandates, resulting in a shift in oversight functions to the informal realm. The aim of this research is to understand how CSOs can gain social legitimacy and exercise pseudo-authoritative authority in the public sphere. To address this, the research methods used include in-depth interviews with 18 informants and analysis of 21 relevant documents. The analysis shows that CSOs' authority is formed through informal socio-political networks that rely on three main factors: community support, closeness to security forces, and local media coverage that strengthens their symbolic legitimacy. This then results in pseudo-authority, a form of de facto authority that is accepted in certain social contexts even though it is not legally recognized. Further findings indicate resistance from business actors and community leaders who question the legality and economic impact of mass organization interventions, which are considered to have the potential to hamper the business climate and create uncertainty. However, the weak response from local governments actually emphasizes the gap in formal oversight mechanisms, opening up space for mass organizations to fill this role. This condition indicates that the authorizing environment is not institutional as it should be, but rather social, contested, and dependent on the dynamics of power relations at the local level. Thus, this study provides a picture of how the pseudo-authority practices of mass organizations are formed, accepted, and questioned in the context of urban social and economic governance.